INVESTIGATION OF DIFFERENTIAL ABSORPTION OF DNA COMPLEXES WITH LIGANDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The investigation of complexes of ethidium bromide (EtBr) and methylene blue (MB) with DNA at 0.02 M Na+ ionic strength of solution has been carried out. Absorption and differential absorption spectra of EtBr and MB and their complexes with DNA were obtained. The isobestic point was revealed on the absorption and differential absorption spectra of EtBr and its complexes with DNA, while on analogous spectra of MB and its complexes with DNA there is no isobestic point.
Keywords: EtBr, MB, absorption spectra, differential absorption spectra, isobestic point